1977
DOI: 10.1177/000331977702800304
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Results of the Medical Treatment of Coronary Artery Disease

Abstract: The natural history of patients with ischemic heart disease varies widely depending upon the anatomic lesion and extent of left ventricular dysfunction. Several clinical variables may also be used to help determine the likelihood of long-term survival. Individuals with high-grade isolated disease of the left anterior descending coronary artery, without significant impairment of ventricular function, have little morbidity and mortality for the 2-year period after arteriography. At the other end of the spectrum,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
2

Year Published

1978
1978
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 12 publications
0
5
0
2
Order By: Relevance
“…4 It is estimated that the first manifestation of coronary artery disease (CAD) in 60-70% of patients is either sudden death or myocardial infarction, whereas only a minority present first with angina or other symptoms of reversible ischemia. 5 The reason for the onset of symptoms late in the disease process is not known but could be related to an impairment in, or inadequate fidelity of the cardiac sensory mechanism responsible for signaling myocardial ischemia. This paper will review evidence for such a reduction in cardiac sensing of ischemia, termed silent myocardial ischemia.…”
mentioning
confidence: 99%
“…4 It is estimated that the first manifestation of coronary artery disease (CAD) in 60-70% of patients is either sudden death or myocardial infarction, whereas only a minority present first with angina or other symptoms of reversible ischemia. 5 The reason for the onset of symptoms late in the disease process is not known but could be related to an impairment in, or inadequate fidelity of the cardiac sensory mechanism responsible for signaling myocardial ischemia. This paper will review evidence for such a reduction in cardiac sensing of ischemia, termed silent myocardial ischemia.…”
mentioning
confidence: 99%
“…Cardiovascular disease is the most frequent cause of death worldwide [ 1 ]. The first manifestation of coronary artery disease in 60–70 % of patients is either sudden death or myocardial infarction (MI) [ 2 ]. Silent myocardial infarction (SMI) relates to absence of symptoms usually associated with myocardial ischemia.…”
Section: Introductionmentioning
confidence: 99%
“…The first manifestation of coronary artery disease in 60–70% of patients is sudden death or MI [ 10 ]. A retrospective study of 193 patients who underwent head and neck reconstructive surgery showed a 3.6% incidence rate of postoperative MI [ 11 ].…”
Section: Discussionmentioning
confidence: 99%